Sustainable spatial development: Concept for an interdisciplinary research programme - Wegener, Michael; Spiekermann, Klaus (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Spatial aspects of spatial development will become a key question of social debate in the coming decades. However, substantial research deficits exist with respect to the interaction between human activities in space and their economic, social and ecological impacts. Obviously, these issues cannot be resolved by individual disciplines, but require a holistic research approach. The article presents an outline of such an interdisciplinary research programme.